The Principles of Legal Certainty for Asset Recovery in the Corruption Law in Indonesia - Rintis Eka A'isyatul Wahab; Aprilliani Kusumawati (UNISSULA, 2026)
An effective asset recovery mechanism contributes directly to the recovery of state finances harmed by corruption. Indonesian law is not yet comprehensive and does not provide adequate legal certainty, especially regarding the recovery of assets resulting from corruption held abroad. The applicable regulations in Indonesia regarding the recovery of assets held abroad are not clearly regulated, and Indonesia has only ratified the UNCAC 2003, but its implementation in national legislation is still limited and has not been followed by clear implementing regulations. This study aims to analyze the principle of legal certainty in Indonesian legislation related to the recovery of assets due to corruption diverted abroad. The research method used was normative with a conceptual approach. The results of the study indicated that Law Number 31 of 1999 and Law Number 20 of 2001 concerning the Eradication of Corruption (UU PTPK) concerning asset recovery did not fully uphold the principle of legal certainty. Meanwhile, the mechanism for confiscating assets abroad still relied on the provisions of the 2003 UNCAC, while Indonesia had only ratified the 2003 UNCAC. Therefore, it is hoped that implementing regulations for the 2003 UNCAC can be formed, as well as changes to existing laws and regulations.